Empathy in Action: Forms of Empathetic Behavior in the Community's Implementation of the Gerak Bareng Social Program - Fajariah, Nurul; Wica, Pratama Yoga; Ridhoh, M. Yunasri; Irawan, Hendri (JED (Jurnal Etika Demokrasi), 2024)
The ever-changing and complex dynamics of societal life give rise to various forms of social issues. One of the common consequences is the loss of empathy, leading individuals to harm or even take the lives of others. This highlights the need to foster empathy in a society constantly facing diverse challenges. One way to achieve this is through civic engagement in social programs implemented by social organizations. Such involvement can reveal various forms of empathetic behavior expressed by the community during the implementation of these programs. This study aims to provide an overview of the forms of empathy behavior reflected in the community through the social program of the Gerak Bareng organization. This research uses a qualitative approach with a case study method. The results showed that the forms of empathic behavior that are manifested in the community through citizen involvement in Gerak Bareng's social programs include compassion, giving and sharing, and cooperation. The role of Gerak Bareng in fostering community empathy is demonstrated through civic engagement in Gerak Bareng's social programs with the formation of empathetic behaviors within the community such as compassion, mutual giving, sharing, and collaboration.